An overview of participatory research and learning processes and their relevance to watershed management and development - Consultative Group on International Agricultural Research (CGIAR System Organization, 2003)
This paper outlines general concepts of participatory research and learning; the relevance of participatory approaches to natural resources management and watershed management in particular; elements of good practice for participatory research and learning in the context of gendered, adaptive watershed management; and considerations for proposal development and review.